EXPERIMENTAL AND PRODUCTION FACILITY FOR ANAEROBIC PROCESSING OF ORGANIC POULTRY WASTE - Kamoliddin Usmonov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article presents the technical characteristics of the plant for the anaerobic processing of organic poultry waste, gives a broad overview of the justification and assessment of the capabilities of the device for obtaining biogas from organic poultry waste, as well as the use of a biogas plant and alternative energy. sources. parameters of an anaerobic processing power plant for the production and fermentation process of organic poultry waste.